Pengaruh Komunikasi Organisasi terhadap Work Engagement melalui Kepuasan Kerja Karyawan Universitas Trisakti - Widiyanto, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to analyze the influence of organizational communication on work engagement through job satisfaction among Trisakti University employees. This research is a quantitative study with a cross-sectional design. Data was obtained from 125 randomly selected respondents using a questionnaire with proven validity and reliability indicators. The data analysis technique uses Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach and SmartPLS 3 software. The results of the study indicate that organizational communication has a positive and significant effect on job satisfaction (path coefficient of 0.791), organizational communication also has a positive and significant effect on work engagement (path coefficient of 0.280), and job satisfaction has a positive and significant effect on work engagement (path coefficient of 0.519). The study concludes that organizational communication enhances job satisfaction and work engagement. Additionally, job satisfaction is an important mediator between organizational communication and work engagement.